Tingkat Utang Yang Dikontrol Ukuran Perusahaan dan Penghindaran Pajak - Hermawati, Karina Yulia; Wardhani, Nurhastuty Kesumo (E-Jurnal Akuntansi, 2024)
In Indonesia, revenues from the tax sector have the largest proportion, but companies often try to avoid or reduce tax obligations cleverly and legally due to various motivations. This research is an extension of research conducted by Wardan & Nurharjanti (2019) using the primary and non-primary consumer goods sectors as research objects, profitability as a moderating variable and company size as a control variable, and using the ETR (Effective Tax Rate) proxy. The population used in the research is companies in the primary consumer goods and non-primary consumer goods sectors listed on the IDX from 2020 to 2022, with a total of 168 company samples using the purposive sampling method and processed with the help of SPSS 25. This research shows that the level of debt has a positive effect on tax avoidance and after controlling for company size, there is a positive and significant relationship (getting stronger) between the level of debt and the tax avoidance variable. Keywords: Audit Committee; Leverage; Profitability; Tax Avoidance